A dynamic slicing-based approach for effective SBFL technique. (3rd March 2021) - Ghosh, Debolina; Singh, Jagannath
Fault finding is an activity to locate the fault or bug present in a software. It is a very time taking job and needs much more effort if done manually. Hence, automated fault localisation is always in high demand which reduces the human effort and also makes the task more accurate. Among different existing debugging techniques, spectrum-based debugging is the most efficient for automated fault localisation. Dynamic program slicing is another technique which can reduce the debugging time by reducing the unaffected source codes depending on slicing criteria. In this paper, we present a spectrum-based fault localisation technique by using dynamic slicing. Context-sensitive slicing is used to diminish fault localisation time and makes the process more effective. SBFL metrics are used in the sliced program to find the suspiciousness score of individual program statements. The efficiency of the proposed approach is evaluated on three open-source programs. From results, we notice that due to dynamic slicing the technique takes less time to find the suspiciousness score of individual statements in the sliced program compared to original program. We have also observed that the programmer needs to inspect less source code to detect the buggy statement. The result says that the proposed approach outperforms the pure spectrum-based fault localisation techniques.